(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
Giovanni Antonio Maggi, Vincenzo Monti’s assistant, took an active part in the revision of the Bassvilliana, as the correspondence between them tests: the letters, archived by Maggi himself, are useful to reconstruct the relationship between the author and his assistant, and between Monti and his printers. The scholarly edition edited by Giovanni Biancardi expores if and how Maggi corrected Monti’s work, always with the approval of the author.